WhatsApp e a notícia no programa CBN João Pessoa: reconfiguração da produção na redação de radiojornalismo - Costa, Adriana Simone da (2017)
The research aims to understand the reconfiguration of journalistic production in the writing of the radio program CBN João Pessoa from the introduction of the multiplatform application WhatsApp as a tool destined to capture information during the daily journalistic making of the radiophonic product. The research also aims to reflect on WhatsApp's interactive ability between radio professionals and the target audience through the application and the use of collaborative logic that engages the radio listener who is also a multiplatform user. The results point to changes in the routine of production in the CBN João Pessoa program due to the introduction of the WhatsApp application as a tool for convergence and link between all the vehicles of the Paraíba Communication Network and for the perception of reconfiguration of affectation of journalists' routine and of the informative speed of the radiophonic from the implantation of multi-aplicative.